Analisis Grammatical-Exegetical Wahyu 3:20 dan Implikasinya Terhadap Relevansi Penggunaan Wahyu 3:20 Dalam Model Penginjilan Kontemporer - Jhon Leonardo Presley Purba; Riang Hati Waruwu; Amran Manullang; Robinson Rimun (Sekolah Tinggi Teologi Berita Hidup, 2022)
Revelation 3:20 is a popular verse that used in contemporary evangelism to encourage the unbelievers to believe in Jesus. Nevertheless, is such usage relevant to the text and context of Revelation 3:20? Using a descriptive qualitative research form with an interpretative model of Grammatical-Exegetical analysis, the aims of this study is to find the theological meaning of Revelation 3:20 and its implications for the relevance of the using of Revelation 3:20 in contemporary evangelistic models. The results of this study conclude that based on the text and context of Revelation 3:20, the usage of this verse in contemporary evangelism toward unbelievers is irrelevant to the text and its context, the meaning of